Microstructural characterization and thermal stability of AlCrFeNiTi + Y2O3 high-entropy alloy nanocomposites prepared by mechanical alloying - Raja Rao, K.; Mohan, Man; Dewangan, Sheetal Kumar; Nagarjuna, Cheenepalli; Lee, Kwan; Ahn, Byungmin (Materials Letters, 2024)
The study focuses on the development of lightweight nanocomposites using a powder metallurgy route. Y2O3 nanoparticles (1, 2, and 3 wt%) are added to an AlCrFeNiTi high-entropy alloy (HEA) matrix. The addition of Y2O3 nanoparticles leads to the formation of a small intermetallic phase in HEA matrix. With increasing Y2O3 wt.%, the size of the crystallites diminishes starting from 32.7 nm (HEA) to 10.3 nm (HEAnC-3). TEM examination reveals that the alloy is nanocrystalline with an average grain size of 39.2 ± 2.1 nm. DSC study indicates that the nanocomposites are stable up to 1000 °C, making them ideal for high-temperature applications.
Keywords: Alloy matrix; Average grain size; DSC studies; High entropy alloys; High-temperature application; Intermetallic-phases; Lightweight materials; Microstructural characterizations; Nanocrystallines; High-entropy alloys; Intermetallic; Lightweight materials; Nanocomposites; Y2O3